Implementation of Smoke-Free Area in Batanghari Regency - Al-Farisyi, M.Sahid; Ridwan, M; Ibnu, Ismi Nurwaqiah (Formosa Journal of Multidisciplinary Research, 2024)
The purpose of this research is to understand in depth the implementation and effectiveness of the No Smoking Area (KTR) policy in Batanghari Regency. The research method used is the Qualitative research method used in this study is the Sequential Exploratory design. Research informants consist of 20 people including 1 supervision. 1 regional regulation maker. 1 smoke-free area coordinator. 1 smoke-free area officer as a key informant and 17 heads of departments in Batanghari district as supporting informants. Data collection through in-depth interview and observation methods. Data analysis using the help of Open code software.